Expression of proliferating cell nuclear antigen, vimentin and fibroblast growth factor receptors in canine mammary gland tumours as potential markers for tumour growth agressiveness and high grade - Sahabi, Kabiru (2014)
Canine mammary gland tumour (CMT) is the most common neoplasm that develops spontaneously in female dogs. In Malaysia, the prevalence, risk factors and the expression of potential prognostic markers in CMT have not been investigated. Thus, the objectives of this study were to determine the prevalence and risk factors of dogs in Malaysia diagnosed with mammary tumours and to determine the prognostic value and association of proliferating cell nuclear antigen (PCNA), Vimentin and fibroblast growth factor receptor (FGFR) with common clinicopathological parameters in CMT. The hypothesis of the study are; CMT is among the common neoplasia in intact female dogs diagnosed at the laboratory; malignant CMT is positive for Vimentin expression and have higher number of cells expressing PCNA; Vimentin and PCNA expressions are related to aggressiveness, proliferation, invasiveness and metastasis of CMT; FGFRs are expressed in CMT tissues. A retrospective study was conducted on CMT diagnosed at the Veterinary Histopathology Laboratory (VHL) of the Faculty of Veterinary Medicine (FVM), Universiti Putra Malaysia (UPM) in the period of 2006 to 2012. The study involving 48 CMT cases showed that the prevalence of CMT among all tumours diagnosed in this laboratory was 39%. Neuter status and breed were associated with CMT, as dogs with CMT were found to be intact and of pure breed. Immunohistochemical staining was performed to determine the expression of PCNA, Vimentin, FGFR2, FGFR3 and FGFR4 in 46 CMT tissues and to evaluate the relationship of their expression level with breed size, age, neuter status, involvement of inguinal mammary gland, number of glands involved, mitotic index, tumour size and grade and postsurgical survival in dogs with CMT. Vimentin expression has no association with any of these clinicopathological parameters and failed to predict the postmastectomy survival in CMT. The PCNA expression was significantly higher (p=0.037) in high grade tumours. Although both Vimentin and PCNA failed to predict postmastectomy survival, a positive significant correlation (p=0.029) was observed between Vimentin and PCNA expression in CMT. High grade tumour was noted in intact dogs (p=0.034) that is significantly associated with poor postmastectomy survival (p=0.028). Forty-five tumours (97.8%) expressed FGFR2 and FGFR3. Forty-two (91.3%) tumours expressed FGFR4. Histopathology grade 3 tumours showed significantly higher (p=0.027) FGFR2 expression. The FGFR3 expression has no association with any clinical or histopathology parameters. Large breed size of dogs (p=0.044) and large tumours (p=0.045) were significantly associated with FGFR4 expression. All of these receptors were not able to predict postsurgical survival in CMT. This study concludes the following; (i) CMT is a common type of tumour diagnosed at the VHL, FPV, UPM with a prevalence of 39%; (ii) age, breed and intact neuter status of a dog contribute significantly to risk of CMT development; (iii) PCNA is a good marker for aggressiveness of tumour growth; (iv) histopathology grading can be used to determine prognosis in CMT; (v) expression of FGFR2 and FGFR4 are potential markers for aggressiveness of tumour growth and tumour stage, respectively. Overall the fibroblast growth factor signalling is a pathway important for the pathogenesis of CMT and may be the potential target for new therapeutics in the disease.